Taxation of International Investments. - Morrison, Thomas A. (The Accounting Review, 1966)
The article reviews the leading tax problems of U.S. investors in foreign companies in 1966. It also considers how accountants with their background in evaluating income measurement can aid in making tax barriers more suitably distributed for companies or individuals in the U.S. who are interested in direct investments abroad. The author concludes that it is true that equitable treatment concerning the imposition of taxes on a party operating in different jurisdictions is a responsibility primarily of the party himself. In addition, he observes that the problems are different from the ones usually found because of the international aspect, but many of them can be better resolved after a fresh look at the income theory angle.